MiRNA-148b regulates radioresistance in non-small lung cancer cells via regulation of MutL homologue 1. Issue 3 (30th June 2016) - Zhai, Guangsheng; Li, Gaozhong; Xu, Bo; Jia, Tongfu; Sun, Yinping; Zheng, Jianbo; Li, Jianbin
Abstract : miR-148b regulates radioresistance of lung cancer cells by modulating MLH1 expression level. Abstract : Radioresistance represents a major obstacle in cancer treatment, the underlying mechanism of which is complex and not well understood. miR-148b has been reported to be implicated regulating radioresistance in lymphoma cells. However, this function has not been investigated in lung cancer cells. Microarray analysis was performed in A549 cells 48 h after exposure to 8 Gy of γ-irradiation or sham irradiation to identify differentially expressed miRNAs. miR-148b mimic and inhibitor were transfected, followed by clonogenic survival assay to examine response to irradiation in A549 cells. Western Blot and luciferase assay were performed to investigate the direct target of miR-148b . Xenograft mouse models were used to examine in vivo function of miR-148b . Our data showed that expression of miR-148b was significantly down-regulated in both serum and cancerous tissues of radioresistant lung cancer patients compared with radiosensitive patients. Overexpression of miR-148b reversed radioresistance in A549 cells. MutL homologue 1 (MLH1) is the direct target of miR-148b which is required for the regulatory role of miR-148b in radioresistance. miR-148b mimic sensitized A549 xenografts to irradiation in vivo . Our study demonstrated that miR-148b regulates radioresistance of lung cancer cells by modulating MLH1 expression level. miR-148b may represent a new therapeutic target for the intervention of lung cancer.